Extraction of volatile oil from the leaves of the myrtle plant Mytrus communis and its effect on some types of Gram-negative and Gram-positive bacteria and Candida albicans yeast. (Journal of the College of Basic Education, 2023)
The volatile oil was extracted from the leaves of the local myrtle plant by the method of hydro-distillationWater distilation method and its effect on the positive and negative type of Gram stain for bacteriaEsherichia coli, Staphylococcus aureus and Candida albicans yeast. The results of the study proved that the extracted myrtle oil had a high inhibitory effect against E.coli, S.aureus and C.albicaus. It was also noted that E.coli bacteria were more sensitive than S.aureus bacteria. Its minimum inhibitory concentration (MIC) is (7700) ppm, and its minimum lethal concentration is (7850) ppm. While the MIC of S. aureus was (8000)ppm and its MBC was (8650)ppm, while Candida albicans was the most resistant, as its MIC reached (9400)ppm and its MFC reached (9550)ppm.